2003
DOI: 10.1177/01634437030255004
|View full text |Cite
|
Sign up to set email alerts
|

Audiences and Readers of Alternative Media: The Absent Lure of the Virtually Unknown

Abstract: Reasons for the virtual absence of research in this area are proposed, and contrasts between users of conventional media and alternative media audiences suggested, along with a political ethics of listening. Connections between social movements and alternative media uses are discussed, the interplay between political consciousness and alternative media use is examined, and social conditions in which the latter are responded to are explored. Finally, the variety of alternative media formats, genres and technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 18 publications
0
84
0
5
Order By: Relevance
“…Our audience study completes examination of the circle of production and consumption, an absence in the research literature on community media identified by many, including Helen Molnar and Michael Meadows (2001), Clemencia Rodriguez (2001), John Downing (2001Downing ( , 2003; Chris Atton (2002).…”
Section: Introductionmentioning
confidence: 70%
“…Our audience study completes examination of the circle of production and consumption, an absence in the research literature on community media identified by many, including Helen Molnar and Michael Meadows (2001), Clemencia Rodriguez (2001), John Downing (2001Downing ( , 2003; Chris Atton (2002).…”
Section: Introductionmentioning
confidence: 70%
“…Various alternative media have previously tried to challenge the dominance of mainstream media and its ways of depicting citizens (e.g. Rodriguez 2001;Downing 2003). The pressures of the mass media to situate itself closer to its audience have in part derived from this activity of alternative media and the international trend of fragmenting audiences (Deuze 2006, 264).…”
Section: Relations Between Citizens and The Mainstream Mediamentioning
confidence: 99%
“…Naturally, this derives from the fact that Manse Square is a place for neighbourhood communication, but probably also the earthiness of the published stories has narrowed the distance. However, close connections between audience and producers have not been self-evident generally within alternative media (Downing 2003).…”
Section: The Development Of Civic Engagementmentioning
confidence: 99%
“…Perhaps this situation is also a strong reminder for us of the heterogeneity of public spheres per se, and the 'ideal' nature of the notion a homogeneous of public sphere. Before the new media era, scholarship on 'alternative media' in different contexts was among the work that addressed such considerations (see, for example, Downing 2003). Peter Dahlgren (2001: 39) points out: 'Democracy needs multiple and alternative public spheres .…”
Section: The New Geopolitics Of Public Spheres In the Era Of Blogsmentioning
confidence: 99%